Penerapan Model Unified Theory Of Acceptence And Use Of Technology (UTAUT 2) Terhadap Perilaku Pelanggan E-Commerce Shopee Indonesia Di Kota Palembang - Andi Nur Sheila Fatihanisya; Susan Dian Purnamasari (Journal of Information System and Informatics, 2021)
The developing of marketplace makes many changes in commerce. Start from conventional way and now become online shopping. One of the biggest marketplace in Indonesia is Shopee. Due to the massive electronic commerce activity, this study aimed to know the factor that influenced behavioral intention and use behavior of shopee’s user. This study adopted UTAUT 2 model which has seven variables; performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivations, price value and habit also moderated by age, gender and experience. The analysis of the model was conducted by using SEM-PLS method and analysed with SmartPLS 3. The data of this study was collected by using questionnaire and designed only for Shopee user who stayed in Palembang. The result show if behavioral intention influenced by social influence with T value is 1.985, P value is 0.048 and F square is 0.105 and also influenced by habit with T value is 4.755, P value is 0,000 and F square is 0,512 which achieved the standart value in this study. In other side, this study show if use behavioral influenced by facilitating condition with 2.762 T value , 0,006 P value and 0,140 F square.